2013
DOI: 10.3389/fcimb.2013.00078
|View full text |Cite
|
Sign up to set email alerts
|

Bloodstream form pre-adaptation to the tsetse fly in Trypanosoma brucei

Abstract: African trypanosomes are sustained in the bloodstream of their mammalian hosts by their extreme capacity for antigenic variation. However, for life cycle progression, trypanosomes also must generate transmission stages called stumpy forms that are pre-adapted to survive when taken up during the bloodmeal of the disease vector, tsetse flies. These stumpy forms are rather different to the proliferative slender forms that maintain the bloodstream parasitaemia. Firstly, they are non proliferative and morphological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
82
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(87 citation statements)
references
References 117 publications
5
82
0
Order By: Relevance
“…Previous experiments in BF cells have demonstrated that VSGs cannot be expressed from two different expression sites at the same high level without a penalty on cellular fitness (Chaves et al ., ; Batram et al ., ). Additionally, BF cells developing to quiescent stumpy forms (Vassella et al ., ; Capewell et al ., ; Rico et al ., ) have the VSG coat present on their surface, in contrast to MF cells that synthesize the VSG coat de novo during their transition to quiescence. Since (i) both MESs and BESs are Pol I gene expression units that produce about 10% of the mRNA and protein in the cell, (ii) compete for binding to the same general transcription initiation factor CITFA (Kolev et al ., ) and (iii) contain very similar VSG pre‐mRNA trans ‐splicing and polyadenylation signals, the choice of MESs over BESs in these cells transitioning to quiescence indicates that not only they cannot support the expression of more than one VSG expression site, but they also cannot support the expression of a single 40–60 kb long BES.…”
Section: Discussionmentioning
confidence: 99%
“…Previous experiments in BF cells have demonstrated that VSGs cannot be expressed from two different expression sites at the same high level without a penalty on cellular fitness (Chaves et al ., ; Batram et al ., ). Additionally, BF cells developing to quiescent stumpy forms (Vassella et al ., ; Capewell et al ., ; Rico et al ., ) have the VSG coat present on their surface, in contrast to MF cells that synthesize the VSG coat de novo during their transition to quiescence. Since (i) both MESs and BESs are Pol I gene expression units that produce about 10% of the mRNA and protein in the cell, (ii) compete for binding to the same general transcription initiation factor CITFA (Kolev et al ., ) and (iii) contain very similar VSG pre‐mRNA trans ‐splicing and polyadenylation signals, the choice of MESs over BESs in these cells transitioning to quiescence indicates that not only they cannot support the expression of more than one VSG expression site, but they also cannot support the expression of a single 40–60 kb long BES.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, stumpy forms, which are preadapted for survival in tsetse, receive an unknown signal and differentiate to insect-stage procyclic forms (reviewed in ref. 38). Stumpy parasites release their VSG coat via a bimodal process that involves GPI hydrolysis by a parasite GPI phospholipase C and endoproteolytic cleavage (39,40).…”
Section: Mammalian Parasite Vsg Coat Proteins Mediate the Cardia Genementioning
confidence: 99%
“…These adaptions also include increased sensitivity to specific environmental cues that signal entry to the tsetse fly vector, as well as resistance to extracellular acidic and proteolytic stress 40, 41 . Given that B-SS are non-proliferative and existent only in pleomorphic strains, it is more difficult to obtain large and pure quantities of this life-cycle stage in vitro .…”
Section: Metabolic Adaptations During the Trypanosoma Brucei Life mentioning
confidence: 99%